Crystallization analysis and determination of Avrami exponents of CuAlNi alloy by molecular dynamics simulation - Celik, Fatih Ahmet; Kazanc, Sefa (Elsevier, 2013)
In this study, local atomic rearrangements of Cu-%26.8Al-%2.5Ni ternary alloys (3 A) are investigated during their crystallization processes from amorphous phase using molecular dynamics (MD) simulations. These simulations are based on the Sutton-Chen type of embedded atom method (SCEAM) that employs many-body interactions. In order to analyse the structural development obtained from MD simulation, the simulation techniques are used as bond order parameter, radial distribution function (RDF). Local atomic bonded pairs and short range order properties in the model alloy have been analysed using the Honeycutt-Andersen (HA) method. The kinetics of the crystallization is described by Johnson, Mehl and Avrami (JMA) model, which has been analysed with MD method by using the crystalline bonded pairs. The simulation results show that the structural variation of local atomic bonded pairs is of great importance to understand the crystallization kinetics from amorphous phase to crystal phase during the crystallization. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Computer simulation; Nanostructures; Recrystallization; Johnson-Mehl and Avrami (JMA) model